2009
DOI: 10.1002/pits.20379
|View full text |Cite
|
Sign up to set email alerts
|

Changes in children's peer interactions following a natural disaster: How predisaster bullying and victimization rates changed following Hurricane Katrina

Abstract: Youth exposed to disasters experience stress and adjustment difficulties, which likely influence their interactions with peers. In this study, we examined changes in bullying and peer victimization in two cohorts of children. Youth from an area affected by Hurricane Katrina were assessed preand postdisaster (n = 96, mean [M] = 10.9 years old, 53% female), and a comparison group from a nearby area was assessed over the same time interval 1 year prior (n = 120, M = 10.2 years old, 52% female). Within the hurrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…Further research has indicated bidirectional relationships between psychological symptoms and peer relational problems, including bullying behaviors and peer victimization experiences (Terranova et al, 2009a; Terranova, Boxer, & Morris, 2009b). Therefore, interventions aiming to reduce children’s post-disaster psychological symptoms could improve peer relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Further research has indicated bidirectional relationships between psychological symptoms and peer relational problems, including bullying behaviors and peer victimization experiences (Terranova et al, 2009a; Terranova, Boxer, & Morris, 2009b). Therefore, interventions aiming to reduce children’s post-disaster psychological symptoms could improve peer relationships.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 articles met the inclusion criteria for data extraction (Fig 1). Seven of the included studies were from the United States [73][74][75][76][77][78][79], two were from Sri Lanka [63,80], one was from Bangladesh [81], and one was from Haiti [82]. Concurrent or recent armed conflict was solely present in Sri Lanka [83], and Haiti had experienced recent political violence [84].…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…Concurrent or recent armed conflict was solely present in Sri Lanka [83], and Haiti had experienced recent political violence [84]. The majority of studies sampled school-going children in addition to their caregivers [63,[76][77][78][79][80], and the age of children spanned from 0 to 18 years of age [63,[73][74][75][76][77][78][79][80][81][82].…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similar reactions may occur in younger school-aged children. Additional research on school-aged youths has documented decreases in academic performance and increased inattention (La Greca & Prinstein, 2002) as well as somatic complaints such as headaches and stomachaches (Hensley & Varela, 2008;NCTSN, n.d.) and aggressive behavior (Terranova, Boxer, & Morris, 2009). Adolescents' reactions are more closely aligned with adult conceptualizations of PTSD, although academic declines (Dyregrov, 2004) and aggressive behavior have also been observed (Marsee, 2008).…”
mentioning
confidence: 99%